Temperature effects on the activity of vectors for Leishmania tropica along rocky habitat gradients in the Eastern Mediterranean. Issue 2 (8th November 2018) - Waitz, Yoni; Paz, Shlomit; Meir, David; Malkinson, Dan
ABSTRACT: Cutaneous leishmaniasis caused by Leishmania tropica, transmitted by Phlebotomus sergenti and Phlebotomus arabicus, has been detected in Israel. This research strives to identify the complexity of temperature effects on vectors of L. tropica and to analyze seasonality and distribution across altitudinal levels. Sand fly trappings were conducted monthly during 2015‐2016 in an endemic region for L. tropica in the eastern Galilee. Trappings were conducted in hyrax den sites across a broad topographic and climatic gradient. Using N‐mixture models, we investigated the activity levels of sand flies as related to temporary and periodic climatic variables. We tested generality of climate‐driven models using Root‐Mean‐Square Error (RMSE) values by comparing the 2015‐2016 data with trapping data from 2013. P. sergenti activity was found to be positively and exponentially correlated with early night temperatures and more strongly correlated with average early‐night temperatures for two weeks. P. arabicus exhibited a linear correlation with temperature. Climate‐driven models for both species yielded lower RMSE values for the 2013 data, which validate the generality of the models. Considerable differences were found in slope coefficients of temperature effect on sand fly activity among sites related to elevation levels, implying differential local responses of sand flies to temperature.